2002
DOI: 10.1074/jbc.m200202200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Role of Residue Gln151 in Error Prone DNA Synthesis by Human Immunodeficiency Virus Type 1 (HIV-1) Reverse Transcriptase (RT)

Abstract: It has previously been reported that mutations in the Gln 151 residue of human immunodeficiency virus type 1 (HIV-1) reverse transcriptase (RT) greatly enhance RT fidelity. In this study, we employed pre-steady state kinetic assays to elucidate the mechanistic role of residue Gln 151 in highly error prone DNA synthesis by HIV-1 RT. Using our Q151N high fidelity mutant, which is structurally altered in its ability to interact with the 3-OH on the sugar moiety of the incoming deoxynucleotide triphosphate (dNTP),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(74 citation statements)
references
References 33 publications
8
66
0
Order By: Relevance
“…The dNTP binding to the active site of the mutant RTs likely becomes a rate-limiting step during the steady-state primer extension reaction at low dNTP concentrations. Overall DNA polymerization capability at the dNTP concentrations found in macrophages is greatest for wild-type RT, followed by V148I RT and then Q151N RT, which displayed the most significant decrease in dNTP binding affinity (14,17). Our kinetic analysis demonstrated that, like these HIV-1 dNTP binding mutants, MuLV RT also has a 40 -75-fold higher k d than wild-type HIV-1 (data not shown).…”
Section: Hiv-1 Replication In Human Primarymentioning
confidence: 80%
See 2 more Smart Citations
“…The dNTP binding to the active site of the mutant RTs likely becomes a rate-limiting step during the steady-state primer extension reaction at low dNTP concentrations. Overall DNA polymerization capability at the dNTP concentrations found in macrophages is greatest for wild-type RT, followed by V148I RT and then Q151N RT, which displayed the most significant decrease in dNTP binding affinity (14,17). Our kinetic analysis demonstrated that, like these HIV-1 dNTP binding mutants, MuLV RT also has a 40 -75-fold higher k d than wild-type HIV-1 (data not shown).…”
Section: Hiv-1 Replication In Human Primarymentioning
confidence: 80%
“…Reaction products were immediately denatured by incubating at 95°C for 5 min, and 4 l of each 30 l of final reaction mixture was quantitated by phosphorimaging analysis (PerkinElmer Life Sciences) of 14% acrylamide-urea denaturing gels (SequaGel, National Diagnostics; model S2 sequencing gel electrophoresis apparatus, Labrepco). Note that in our purification protocol, ϳ30 -60% of the purified RT protein was active as determined by our pre-steady-state kinetic assay using a similar 18-mer/40-mer primer/ RNA template (17,18). The reaction with less RT (10 nM), which is still a higher concentration than the highest dNTP concentration used (6.4 nM), gave a similar incorporation profile under the assay condition.…”
Section: Single Nucleotide Incorporation Assaymentioning
confidence: 98%
See 1 more Smart Citation
“…HIV-1 RT was subsequently expressed in Escherichia coli BL21 (DE3) and purified with nickel-nitrilotriacetic acid chromatography followed by DEAE and SP anion exchange as described previously (23). These RT proteins were quantified and stored in 10% glycerol dialysis buffer as described previously (24,25).…”
Section: Methodsmentioning
confidence: 99%
“…We recently isolated two HIV-1 RT mutants, V148I and Q151N, that specifically exhibit reduced dNTP binding affinity (1/K d ) without a change in catalysis (k pol ) (16,17). Kinetic and structural analyses suggested that these mutations interfered with H-bond formation between the side chain of the Gln-151 residue and the 3Ј-OH group of the incoming dNTP substrate (18).…”
mentioning
confidence: 99%